Water-based high-temperature baking finish paint and preparation method thereof
By optimizing the resin system and additive ratio of water-based high-temperature baking topcoat, the shortcomings of existing water-based high-temperature baking paint in the spray process are solved, and a variety of spraying methods and equipment are realized, which improves the performance and attachment of the paint film. Focus on supporting the 'oil to water' policy of the industrial paint industry.
Patent Information
- Application Number
- CN202411486267.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-07
AI Technical Summary
The existing water-based high-temperature paint has insufficient application in the spraying process, which is difficult to adapt to a variety of construction processes and spraying equipment, especially in air-based spraying and electrostatic spraying, which has affected the 'oil to water' policy of the industrial paint industry. The implementation of
Provide an aqueous high-temperature baking topcoat, by optimizing the resin system, including polyurethane acrylate, hydroxyacrylic resin, acrylic copolymer, polyester resin and amino resin, control the mass ratio of each resin and the ratio of additives, making it suitable Various spraying methods and equipment.
This water-based high-temperature baking topcoat can be used for a variety of spraying methods and equipment, especially in air spraying and electrostatic spraying, which improves the resistance, mechanical properties and adhesion of the paint film, and supports the oil-to-water conversion of the industrial paint industry in the oil-to-water 'policy.
Smart Images

Figure BDA0005098784720000051 
Figure BDA0005098784720000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water-based high-temperature baking varnish, in particular to a water-based high-temperature baking topcoat and a preparation method thereof. Background Art
[0002] In the coating industry, coatings that need to be baked to form a dry film are called baking paints, and coatings with a film-forming temperature above 140°C are commonly known as high-temperature baking paints. At present, most of the industrial paint industry uses oil-based baking paints. Because a large amount of petroleum raw materials (such as benzene, alcohol, ether, etc.) are needed as solvents, on the one hand, it consumes petroleum resources, and on the other hand, organic solvents are easy to volatilize, which will produce a large amount of VOCs (volatile organic compounds), causing environmental pollution and even endangering human health. In addition, the large amount of petroleum organic solvents will bring hidden dangers in terms of safety, so high safety precautions must be spent.
[0003] Compared with oil-based paints, most of the original organic solvents in water-based paints are replaced by water, which becomes the main solvent. This makes water-based paints have obvious positive effects in terms of green environmental protection and carbon emission control. At present, there are various water-based high-temperature baking paints on the market. Since the domestic paint industry is generally in the transition stage of "oil to water", most companies usually use the old oil-based paint process and equipment when switching to water-based paints due to cost reasons. However, there is a large difference between the main solvents of water-based paints and oil-based paints, which brings a series of equipment applicability problems, especially air spraying and electrostatic spraying processes and equipment. Therefore, there is an urgent need for a water-based paint that can solve the above technical problems. A Chinese patent (application number CN107325661A) discloses a high-temperature baking topcoat for shared bicycles without glazing and a preparation method thereof. By optimizing the coating process to a two-coating and two-baking process, the baking paint provided is equivalent to the effect of oil-based paint, but the applicability of the spraying process needs to be further optimized. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a water-based high-temperature baking topcoat, which can be applicable to a variety of spraying methods (air spraying, electrostatic spraying), adapt to a variety of construction processes and spraying equipment, and can be applied to oil-based paint equipment after simple equipment cleaning, parameter resetting and process conversion. It is particularly outstanding in air spraying and electrostatic spraying, and plays a positive role in the implementation of the "oil to water" policy in the industrial paint industry.
[0005] On one hand, the present invention provides a water-based high-temperature baking topcoat, which comprises, by mass percentage, at least 5-10% of polyurethane acrylate, 7-18% of hydroxyl acrylic resin, 5-15% of acrylic copolymer, 10-20% of polyester resin, 3-9% of amino resin, 1-40% of additives, and deionized water to make up the balance.
[0006] As a preferred technical solution, the mass ratio of the polyurethane acrylate, hydroxy acrylic resin, acrylic copolymer, polyester resin and amino resin is (7.5-9): (11-14): (5.5-10): (15-19.5): (3-9).
[0007] As a preferred technical solution, the viscosity (25°C) of the polyurethane acrylate is 20-1000mPa.s, preferably 20-200mPa.s, and the model is APU 10620.
[0008] As a preferred technical solution, the hydroxy content of the hydroxy acrylic resin is 1-4wt%, preferably 2.0-3.3wt%, most preferably 2.2wt%, and the model is AQUAPA-8222.
[0009] As a preferred technical solution, the polyester resin is a water-soluble polyester resin, the viscosity of the water-soluble polyester resin (23°C, Brookfield RVT, 10S-1, ISO 3219) is 2-7 Pa.s, preferably 3.8-5.0 Pa.s, and the model is Allnex 6407.
[0010] As a preferred technical solution, the amino resin is etherified high-imino melamine, the dynamic viscosity (25° C.) of the etherified high-imino melamine is 1000-8000 mPa.s, preferably 2000-4600 mPa.s, and the model is Allnex CYMEL 325.
[0011] As a preferred technical solution, the viscosity (25°C) of the acrylic copolymer is 100-5000mPa.s, preferably 500-3000mPa.s, and the model is Oubaodi AS2688.
[0012] As a preferred technical solution, the additive includes at least one of a defoamer, a leveling agent, a pH adjuster, an adhesion promoter, a cosolvent, a dispersant, a rheological additive, a pigment, and a filler.
[0013] Preferably, based on the total mass of the water-based high-temperature baking topcoat, the additives include 0.1-1% defoamer, 0.1-1% leveling agent, 0.1-2% pH adjuster, 0.1-1% adhesion promoter, 1-10% cosolvent, 0.1-3% dispersant, 0.1-2% rheological additive, 0.1-3% pigment, and 1-15% filler.
[0014] As a preferred technical solution, the defoamer is a non-silicon defoamer, preferably Evonik Surfynol 104E.
[0015] As a preferred technical solution, the leveling agent is a non-silicone leveling agent, preferably BYK-3560.
[0016] As a preferred technical solution, the pH regulator is dimethylethanolamine (DMEA).
[0017] As a preferred technical solution, the adhesion promoter is Digo Addbond DS 1300.
[0018] As a preferred technical solution, the co-solvent is selected from at least one of BCS (ethylene glycol monobutyl ether) and DPNB (dipropylene glycol butyl ether), preferably a combination of ethylene glycol monobutyl ether and dipropylene glycol butyl ether, and the mass ratio of ethylene glycol monobutyl ether and dipropylene glycol butyl ether is (1-3): (2-5), preferably 1:2.
[0019] As a preferred technical solution, the dispersant is a combination of TEGO 755W and TEGO 757W, and the mass ratio of TEGO 755W to TEGO 757W is 1:(0.5-2), preferably 1:1.
[0020] As a preferred technical solution, the rheological additive is Hemmings 299
[0021] As a preferred technical solution, the filler is selected from at least one of talc, barium sulfate and calcium carbonate, preferably a combination of talc and barium sulfate. The mass ratio of talc to barium sulfate is (10-15): (1-3), preferably 11:2.
[0022] The topcoat provided by the present invention adopts a resin system including polyurethane acrylate, hydroxyl acrylic resin, acrylic copolymer, polyester resin and amino resin, and further controls the addition amount of each resin in the system, so that the topcoat provided can be applied to a variety of substrate surfaces for spraying, and the paint film has high tolerance, good mechanical (bump resistance) performance, and strong adhesion to a variety of substrates. In particular, the mass ratio of polyurethane acrylate, hydroxyl acrylic resin, acrylic copolymer, polyester resin, and amino resin in the control system is (7.5-9): (11-14): (5.5-10): (15-19.5): (3-9), and under the coordination of additives, the gloss, flexibility, impact resistance and adhesion of the topcoat are guaranteed at the same time, better meeting the actual application requirements, while under the product formula system of the present invention, the addition ratio of acrylic copolymer exceeds 15%, resulting in excessive hardness of the paint film, easy brittleness after high temperature, resulting in poor impact resistance, flexibility and adhesion performance; the addition ratio of polyester resin is less than 10%, which will cause the gloss of matte paint to be unstable, the total proportion of adhesion promoter usage is less than 0.3%, and the adhesion performance is reduced.
[0023] The topcoat provided by the present invention can accurately control the gloss, realize a variety of colors (varnish, solid color, metallic paint), and realize good operability with easy regulation and wide construction window at the spraying process level. It overcomes the problem that the edge tip or the angle of the connecting surface is difficult to paint due to the small size and complex shape of the workpiece in some industries, which makes it difficult to meet the requirements of film thickness or even expose the bottom, and cannot form an effective protective coating. At the same time, it effectively avoids the construction problems of spraying wet film sagging, bubbling, bottom paint accumulation, etc., and better meets the actual needs.
[0024] Another aspect of the present invention provides a method for preparing a water-based high-temperature baking topcoat, comprising at least the following steps:
[0025] (1) adding (50-70) wt% of deionized water into a pull cylinder, adding a dispersant and (20-40) wt% of a defoamer while stirring at (200-300 rpm), continuing to stir after being evenly dispersed, and adding a pigment and a filler in sequence while stirring at (200-300 rpm), stirring for 30-60 minutes to prepare a slurry; grinding the slurry using a grinder until the fineness reaches less than 20 μm;
[0026] (2) polyurethane acrylate, hydroxyl acrylic resin, acrylic copolymer, polyester resin, and amino resin are sequentially added into a kettle under stirring (200-300 rpm), and then pH adjuster, remaining defoamer, leveling agent, adhesion promoter, rheological additive, and cosolvent are added in order, with a feeding interval of 2-3 minutes; then the speed is increased to 500-600 rpm, and the remaining deionized water is uniformly added to a position 2-3 cm away from the center of the vortex, and the total water addition time is controlled to be 15-20 minutes; after the deionized water is added, high-speed dispersion (800-1000 rpm) is performed for 30-60 minutes to obtain a mixed material;
[0027] (3) After high-speed dispersion is completed, the slurry prepared in step (1) is uniformly added to the mixed material obtained in step (2), the rotation speed is reduced to 500-600 rpm, the slurry feeding time is controlled to be 10-15 minutes, and stirring is continued for 30-60 minutes after the feeding is completed.
[0028] Beneficial Effects
[0029] 1. The present invention provides a water-based high-temperature baking topcoat, which can be applied to a variety of spraying methods (gas spraying, electrostatic spraying), adapt to a variety of construction processes and spraying equipment, and can be applied to oil-based paint equipment after simple equipment cleaning, parameter resetting and process conversion. It is particularly outstanding in gas spraying and electrostatic spraying, and plays a positive role in promoting the "oil-to-water" policy in the industrial paint industry.
[0030] 2. The topcoat provided by the present invention adopts a resin system including polyurethane acrylate, hydroxyl acrylic resin, acrylic copolymer, polyester resin and amino resin, and further controls the addition amount of each resin in the system, so that the provided topcoat can be suitable for spraying on the surface of various substrates, and the paint film has high resistance, good mechanical (bump resistance) performance, and strong adhesion to various substrates.
[0031] 3. The present invention controls the mass ratio of polyurethane acrylate, hydroxyl acrylic resin, acrylic copolymer, polyester resin and amino resin in the system to (7.5-9): (11-14): (5.5-10): (15-19.5): (3-9). With the cooperation of additives, the gloss, flexibility, impact resistance and adhesion of the topcoat are guaranteed at the same time, thus better meeting the actual application requirements.
[0032] 4. The topcoat provided by the present invention can accurately control the gloss and achieve a variety of colors (varnish, solid color, metallic paint), and achieve good operability with easy regulation and a wide construction window at the spraying process level.
[0033] 5. The present invention overcomes the problem that the edge tips or the angles of the connecting surfaces are difficult to paint due to the small size and complex shape of the workpieces in some industries, which makes it difficult to meet the film thickness requirements or even expose the bottom, and it is impossible to form an effective protective coating. At the same time, it effectively avoids construction problems such as spray wet film sagging, bubbling, and paint accumulation on the bottom, and better meets actual needs. DETAILED DESCRIPTION
[0034] The types and sources of the raw materials in the examples and comparative examples of the present invention are as follows:
[0035] Polyurethane acrylate: APU 10620
[0036] Hydroxylated acrylic resin: Jiangsu Fuqisen New Materials Co., Ltd. AQUAPA-8222
[0037] Acrylic copolymer: OBODI AS2688
[0038] Polyester resin: Allnex 6407
[0039] Amino resin: Allnex CYMEL 325
[0040] Non-silicone defoamer: Evonik Surfynol 104E
[0041] Non-silicone leveling agent: BYK-3560
[0042] pH adjuster: DMEA
[0043] Adhesion promoter: Digo Addbond DS1300
[0044] Cosolvent 1: BCS
[0045] Cosolvent 2: DPNB
[0046] Dispersant 1: TEGO 755W
[0047] Dispersant 2: TEGO 757W
[0048] Rheological additive: Hemmings 299
[0049] Pigment 1: Titanium dioxide (Longmang titanium dioxide R-996)
[0050] Pigment 2: Carbon black (Mitsubishi Carbon Black MA-100)
[0051] Pigment 3: DIC high temperature resistant organic pigment red powder SUNPLAST 228-6864
[0052] Filler 1: Barium sulfate (Sahliben Blanc Fixe micro)
[0053] Filler 2: Talc powder (Guangfu Building Materials (Jiaoling) Refining Co., Ltd.).
[0054] Examples 1-3, Comparative Examples 1-3
[0055] On the one hand, Examples 1-3 and Comparative Examples 1-3 of the present invention provide a water-based high-temperature baking topcoat, and the formula is shown in Table 1 in terms of mass percentage.
[0056] Table 1
[0057]
[0058]
[0059] On the other hand, Examples 1-3 and Comparative Examples 1-3 of the present invention provide a method for preparing a water-based high-temperature baking topcoat, comprising the following steps:
[0060] (1) 60 wt% (based on the total amount of deionized water added) of deionized water is added into a pull cylinder, and a dispersant and 30 wt% (based on the total amount of defoamer added) of a defoamer are added under stirring (300 rpm), and the mixture is stirred evenly. A pigment and a filler are added in sequence under stirring (300 rpm), and the mixture is stirred for 40 minutes to form a slurry; the slurry is ground using a grinder until the fineness reaches less than 20 μm;
[0061] (2) polyurethane acrylate, hydroxyl acrylic resin, acrylic copolymer, polyester resin, and amino resin are sequentially added into a kettle under stirring (300 rpm), and then pH adjuster, remaining defoamer, leveling agent, adhesion promoter, rheological additive, and cosolvent are added in order, with a feeding interval of 3 minutes; then the speed is increased to 600 rpm, and the remaining deionized water is uniformly added to a point 3 cm away from the center of the vortex, and the total water addition time is controlled within 20 minutes; after the deionized water is added, high-speed dispersion (1000 rpm) is performed for 40 minutes to obtain a mixed material;
[0062] (3) After high-speed dispersion is completed, the slurry prepared in step (1) is uniformly added to the mixed material obtained in step (2), the rotation speed is reduced to 600 rpm, the slurry feeding time is controlled to be 15 minutes, and stirring is continued for 40 minutes after the feeding is completed.
[0063] Performance Testing
[0064] The topcoats provided in Examples 1-3 and Comparative Examples 1-3 of the present invention were subjected to the tests listed in Table 2. The test methods are as follows. The test results are shown in Table 2.
[0065] 1. Paint color and appearance: Visually inspect the paint surface to see that the color is uniform, without particles, pinholes, bubbles or wrinkles.
[0066] 2. Fineness
[0067] 2.1 Test conditions and methods:
[0068] 1) Make a prediction to determine the most suitable fineness plate specifications and the approximate grinding fineness of the sample, and choose 50 microns or 100 microns.
[0069] 2) Place the thoroughly cleaned and dried fineness plate on a flat, level, non-slip surface.
[0070] 3) Pour a sufficient amount of sample into the deep end of the groove and allow the sample to slightly overflow. Be careful not to allow air to be entrained in the sample when pouring the sample.
[0071] 4) Hold the scraper with the thumb and index finger of both hands, place the blade of the scraper on the deepest end of the groove of the fineness plate, contact the surface of the fineness plate, and make the long side of the scraper parallel to the wide side of the fineness plate. Moreover, press the scraper vertically on the surface of the fineness plate, so that the long side of the scraper and the groove form a right angle. In 1 to 2 seconds, scrape the scraper at a uniform speed across the entire surface of the fineness plate to the end where the groove depth is 0. Apply enough pressure on the scraper so that the groove is filled with the sample and the excess sample is scraped off.
[0072] 5) After scraping the sample, observe the fineness plate from the side as quickly as possible (within 5 seconds) in the following way. When observing, the line of sight is at right angles to the long side of the groove and the angle with the surface of the fineness plate is 25±5°. At the same time, the observation is required to be made under light that makes it easy to see the condition of the sample in the groove.
[0073] 6) Observe the sample first, except for the dense particle points, especially the position containing 5 to 10 particles in the strip across the groove 3mm. The scattered points that may appear above the dense particle points can be ignored. Determine the position of the upper limit of this strip, and the reading accuracy is 5μm (range is 100μm), 2μm (range is 50μm), and 1μm (range is 25μm).
[0074] 7) Immediately after reading the number, clean the fineness plate and scraper carefully with a suitable solvent.
[0075] 3. Viscosity
[0076] 3.1 Test conditions and methods:
[0077] 1) Before and after the measurement, wipe the viscometer clean with gauze dipped in solvent, and dry it or blow it dry with cold air. Check against the light, and keep the viscometer nozzle clean.
[0078] 2) Stir the sample evenly and adjust the sample temperature to 25±1℃.
[0079] 3) Adjust the viscometer to a horizontal position and place a 150 mL beaker under the viscometer nozzle.
[0080] 4) Block the nozzle with your finger, fill the viscometer with the sample at a temperature of 25±1℃, and use a glass rod or glass plate to scrape the bubbles and excess sample into the groove of the 4# cup.
[0081] 5) Quickly remove your finger and start the stopwatch at the same time, and stop it immediately when the sample flow is just interrupted. The stopwatch reading is the sample outflow time (s).
[0082] 4. pH
[0083] 4.1 Test conditions and methods:
[0084] 1) Clean the electrode tip with distilled water and then clean it again with the solution to be tested.
[0085] 2) Immerse the electrode in the solution to be tested, stir the solution with a glass rod to make it uniform, and read the pH value of the solution on the display.
[0086] 5. Sagging
[0087] 5.1 Test conditions and methods:
[0088] 1) Test conditions: temperature 25±2°C, relative humidity 50±5%.
[0089] 2) Ensure that the sag tester and test plate are clean and dry before use.
[0090] 3) Place the base of the tester on a platform, and then place the test plate in a suitable position on the base. Place the applicator on the top of the test plate with the scale facing the operator.
[0091] 4) Stir the sample thoroughly, place enough sample in the opening in front of the scraper, hold the two ends of the scraper with both hands, make one end always touch the guide edge of the base, and scrape steadily and continuously from top to bottom, while keeping it straight and without ups and downs. This operation should be completed in about 2 to 3 seconds. The excess paint flows into the groove of the base.
[0092] 5) The coated test panel should be immediately inserted into the observation rack and placed vertically. When placing the test panel, the strip film should remain horizontal and the top should be thin and the bottom should be thick.
[0093] 6) After the coating is dry, observe its sagging. If the paint film of this thickness does not flow into the next thickness film, the coating of this thickness does not sag. The area within 20mm at both ends of the coating is not counted.
[0094] 7) The same sample is tested in parallel on three samples. The test results are expressed as the maximum wet film thickness of the coating without sagging measured on no less than two samples (in μm).
[0095] 6. Air spraying construction operation and paint film appearance
[0096] 6.1 Air spraying construction operation method:
[0097] The best construction environment temperature is 25±10℃. Add the diluent (water) to the product at a mass ratio of 15%, stir for 10 minutes, let it stand for 10 minutes, and then start construction after the bubbles are eliminated. The optimum construction viscosity is 30±10s. After spraying, pre-bake at 60℃ for 10 minutes and then high-temperature bake. The high-temperature baking process is 140℃ for 30 minutes.
[0098] 6.2 Paint film color and appearance:
[0099] 1) The sample plate should be sprayed with a uniform paint film without spots, blank spaces or overflow.
[0100] 2) There are no particles or sagging on the surface of the paint film.
[0101] 3) After the coating is completely dry, measure the coating thickness.
[0102] 4) Observe the appearance of the coating film, and ensure it is smooth and free of defects, such as shrinkage cavities, bubbles, pinholes, particles, cracks, etc.
[0103] 7. Gloss
[0104] 7.1 Test conditions and methods:
[0105] 1) Calibrate the gloss meter.
[0106] 2) Take measurements three times at different locations on the sample and calculate the average value.
[0107] 8. Paint film thickness
[0108] 8.1. Test conditions and methods:
[0109] 1) Calibrate the film thickness meter.
[0110] 2) Take measurements three times at different locations on the sample and calculate the average value.
[0111] 9 Pencil hardness
[0112] 9.1 Experimental conditions and methods
[0113] 1) Use a special mechanism pencil sharpener to shave off 5 to 6 mm of wood from each pencil, carefully working to leave the pencil lead in its original, unscratched, smooth cylindrical shape.
[0114] 2) Hold the pencil vertically and keep it at a 90° angle to the sandpaper. Move the pencil back and forth on the sandpaper to smooth the end of the pencil lead. Continue moving the pencil until you get a flat, smooth, circular cross-section with no chips or nicks on the edges. (Repeat this step before each use of the pencil.)
[0115] 3) Insert the pencil into the test instrument and fix it with a clamp to keep the instrument horizontal and the pencil end on the paint film surface.
[0116] 4) As soon as the end of the pencil contacts the paint film, push the pencil away from the operator at a slow and even speed, and push it a long enough distance to make a visual judgment.
[0117] 5) After 30 seconds, wipe the surface of the paint film with a soft cloth or cotton swab dipped in a solvent that has no effect on the paint film. After all the pencil debris on the surface of the paint film has been wiped off, check for defects.
[0118] 6) The pencil hardness of the paint film is expressed as the hardest pencil hardness that does not cause defects in the paint film.
[0119] 10. Flexibility
[0120] 10.1 Experimental conditions and methods
[0121] 1) Insert the test plate from above between the bending part and the shaft rod, with the coating to be tested facing away from the shaft rod. Pull the adjusting bolt to move the thrust bearing so that the test plate is in a vertical position and in contact with the shaft. Fix the test plate by rotating the adjusting jaw. Turn the screw handle to bring the bending part into contact with the coating. The actual bending process is to lift the screw handle and turn it 180° within 1 to 2 seconds, so that the test plate is also bent 180°.
[0122] 11. Impact resistance
[0123] 11.1 Experimental conditions and methods
[0124] Fix the hammer position of the paint film impactor at the 50cm ruler, place the test sample and the test area at the bottom of the instrument horizontally and fix them well. Now let the hammer fall naturally and hit the test area on the test plate, and the impact resistance test is completed. Observe the test results visually or with the help of a magnifying glass. Parallel measurements are performed more than three times to eliminate accidental factors.
[0125] 12. Adhesion
[0126] 12.1 Experimental conditions and methods
[0127] The test adopts the hundred-grid method, using a blade to cut 11 parallel cuts in the coating, and cut another 11 parallel cuts perpendicular to the first cut, with a cut spacing of 1mm. Clear all loose coating fragments. Visually inspect the cut area, use special 3M tape to stick and tear the test area, and then compare the coating status of the test area with the six-level grading standard.
[0128] 13. Neutral salt spray resistance
[0129] 13.1 Experimental conditions and methods
[0130] The temperature in the salt spray chamber should be (35±2)℃. For a horizontal spray collection device with an area of 80cm2, the average collection rate of the salt spray solution measured in a minimum period of 24h should be 1~2.5mL / h. The sodium chloride concentration of the collected solution should be (50±10)g / L and the pH value should be 6.5~7.2. The sprayed test solution should not be reused. Three parallel measurements should be made and the test panels should be checked regularly, while paying attention not to damage the test surface. The test panels should be checked quickly and the salt spray chamber should not be stopped for more than 30min in any 24h. The test panels are not allowed to dry out. If possible, they should be checked at the same time every day. At the end of the specified test period, remove the test panels from the equipment and rinse with clean warm water to remove the test solution residues on the surface of the test panels. Then dry the test panels immediately and check for damage to the surface of the test panels, such as blistering, rust, and rust from scratches.
[0131] 13.2 Criteria
[0132] There is no blistering or rust on the board surface after 150h; there is slight blistering and rust expansion at the cross-section ≤2mm.
[0133] Table 2
[0134] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Paint film appearance qualified qualified qualified qualified qualified qualified Fineness ≤20μm ≤20μm ≤20μm ≤20μm ≤20μm ≤20μm Viscosity 108s 119s 104s 102s 101s 106s pH 8.4 8.5 8.4 8.3 8.6 8.4 Sagging ≥150μm ≥150μm ≥150μm ≥150μm ≥150μm ≥150μm Gloss (60°) 53 59 54 56 32 (failed) 54 Film thickness 32 32 31 31 33 32 hardness 2H 2H 2H 3H 2H 2H Flexibility 2mm 2mm 2mm Failure 2mm 2mm Impact resistance 50kg cm 50kg cm 50kg cm Failure 50kg cm Failure Adhesion Level 0 Level 0 Level 0 Level 1 Level 0 Level 2 (Unqualified) Neutral salt spray resistance ≥400h ≥400h ≥400h ≥400h ≥400h ≥400h
Claims
1. A water-based high-temperature baking topcoat, characterized in that: Calculated by mass percentage, it includes at least 5-10% of polyurethane acrylate, 7-18% of hydroxyl acrylic resin, 5-15% of acrylic copolymer, 10-20% of polyester resin, 3-9% of amino resin, 1-40% of additives, and deionized water to make up the balance.
2. The water-based high-temperature baking topcoat according to claim 1, characterized in that: The mass ratio of the polyurethane acrylate, hydroxy acrylic resin, acrylic copolymer, polyester resin and amino resin is (7.5-9): (11-14): (5.5-10): (15-19.5): (3-9).
3. The water-based high-temperature baking topcoat according to claim 2, characterized in that: The additives include at least one of a defoamer, a leveling agent, a pH regulator, an adhesion promoter, a cosolvent, a dispersant, a rheological additive, a pigment, and a filler.
4. The water-based high-temperature baking topcoat according to claim 3, characterized in that: The viscosity of the polyurethane acrylate at 25° C. is 20-1000 mPa.s.
5. The water-based high-temperature baking topcoat according to claim 4, characterized in that: The hydroxyl content of the hydroxy acrylic resin is 1-4 wt %.
6. The water-based high-temperature baking topcoat according to claim 5, characterized in that: The polyester resin is a water-soluble polyester resin, and the viscosity of the water-soluble polyester resin at 23° C. is 2-7 Pa.s.
7. The water-based high-temperature baking topcoat according to claim 6, characterized in that: The amino resin is etherified high-imino melamine, and the etherified high-imino melamine has a dynamic viscosity of 1000-8000 mPa.s at 25°C.
8. The water-based high-temperature baking topcoat according to claim 7, characterized in that: The viscosity of the acrylic copolymer at 25° C. is 100-5000 mPa.s.
9. The water-based high-temperature baking topcoat according to claim 8, characterized in that: The filler is selected from at least one of talc, barium sulfate and calcium carbonate.
10. A method for preparing a water-based high-temperature baking topcoat according to any one of claims 1 to 9, characterized in that: At least the following steps are included: (1) adding (50-70) wt% of deionized water into a pull cylinder, adding a dispersant and (20-40) wt% of a defoamer under stirring, continuing to stir after being evenly dispersed, and adding a pigment and a filler in turn under stirring, stirring for 30-60 minutes to prepare a slurry; grinding the slurry with a grinder until the fineness reaches less than 20 μm; (2) polyurethane acrylate, hydroxyl acrylic resin, acrylic copolymer, polyester resin, and amino resin are sequentially added into a kettle under stirring, and then pH adjuster, remaining defoamer, leveling agent, adhesion promoter, rheological additive, and cosolvent are added in order, with a feeding interval of 2-3 minutes; then the speed is increased to 500-600 rpm, and the remaining deionized water is uniformly added to a position 2-3 cm away from the center of the vortex, and the total water addition time is controlled to be 15-20 minutes; after the deionized water is added, high-speed dispersion is performed for 30-60 minutes to obtain a mixed material; (3) After high-speed dispersion is completed, the slurry prepared in step (1) is uniformly added to the mixed material obtained in step (2), the rotation speed is reduced to 500-600 rpm, the slurry feeding time is controlled to be 10-15 minutes, and stirring is continued for 30-60 minutes after the feeding is completed.
Citation Information
Patent Citations
Glazing-free high-temperature baked finishing coat for sharing bicycle and preparation method thereof
CN107325661A
Water-based wood coating for electrostatic spraying of rotary cup and preparation method thereof
CN111334154A
Water-based paint and preparation method thereof
CN112680050A
High-resistance water-based metal matte stoving varnish for computer case and preparation method of high-resistance water-based metal matte stoving varnish
CN114806299A
Aqueous coating composition and paint film formed therefrom
CN116426181A